2009
DOI: 10.5650/jos.58.177
|View full text |Cite
|
Sign up to set email alerts
|

Partition Coefficients of 1-Alkanols between Water and DDAB Vesicle Membrane Determined by Differential Conductivity Method

Abstract: The partition coefficients of 1-alkanols between water and didodecyldimethylammonium bromide (DDAB) vesicle membrane, and the change of the degree of counter-ion dissociation on DDAB vesicle caused by the solubilization of 1-alkanols were determined from electric conductivity measurements. A good linear relationship was obtained between logarithmic value of the partition coefficient and carbon number of alkyl chain in 1-alkanols. The standard transfer free energy change per methylene group was evaluated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Unlike CVC (see Table S1 and S2 and Refs. [16][17][18][19][20][21]), T m (Table S3) is well-defined for DDAB in water (T m ≈ 16 • C) and highly cooperative (peak width T 1/2 < 0.5 • C) [2,5,13]. To the best of our knowledge the reverse liquid crystalline-to-gel transition temperature (T m ), has not been reported for DDAB so far because of its exceedingly slow kinetics [3,13].…”
Section: Thermal Behavior Of Ddab In Watermentioning
confidence: 95%
“…Unlike CVC (see Table S1 and S2 and Refs. [16][17][18][19][20][21]), T m (Table S3) is well-defined for DDAB in water (T m ≈ 16 • C) and highly cooperative (peak width T 1/2 < 0.5 • C) [2,5,13]. To the best of our knowledge the reverse liquid crystalline-to-gel transition temperature (T m ), has not been reported for DDAB so far because of its exceedingly slow kinetics [3,13].…”
Section: Thermal Behavior Of Ddab In Watermentioning
confidence: 95%
“…We have applied this technique to didodecyldimethylammonium bromide DDAB vesicles/1-alkanols system, and evaluated the two quantities, i.e., K x and dα / dX a m 7 . By comparing the results of DDAB vesicles/1-alkanols system with those of SDS micelles/1-alkanols one, it was suggested that both of surfactant molecules and 1-alkanol molecules are packed more closely in DDAB vesicle membranes than in SDS micelles 7 .…”
Section: Introductionmentioning
confidence: 99%